Implementasi Ajaran Paravidya dan Aparavidya Dalam Memerangi Hoax Sebagai Upaya Membangun Sumber Daya Manusia Hindu Unggul - Dewa Ayu Putu Tuty Setiarsih; Gede Agus Siswadi (Jayapangus Press, 2023)
Social media basically has a big influence on the dimensions of human life, because humans in their various activities cannot be separated from the existence of social media. Social media will have a good impact, if people understand and use it wisely, but it will have a bad impact if they don't use it wisely. This research principally aims to understand how Hindu teachings are to be wise and critical in managing information on social media, bearing in mind that there are two types of knowledge in Hinduism namely Paravidya and Aparavidya. The method used in this study is a qualitative method with a critical discourse analysis approach. The results of this study indicate that Paravidya and Aparavidya knowledge is the main basis that must be understood by Hindus in relation to managing information on social media. By having these two knowledges, humans can have a balance between worldly and spiritual life. In addition, the teachings of Paravidya and Aparavidya are used as a basis for analyzing further information in the process of pratyaksa pramana (namely by direct observation using the five senses), anumana pramana understands the phenomena that occur by examining them through the causal process, then upamana pramana namely through doing the process of comparison or comparison, and pramana's words, namely through instructions from people who have authority about this information. By understanding this, Hindus will be wise in controlling the information they obtain on social media.